2006
DOI: 10.1104/pp.105.072678
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Functional Conservation, Sufficiency, and Proteolytic Processing of the CLAVATA3 CLE Domain

Abstract: Arabidopsis (Arabidopsis thaliana) CLAVATA3 (CLV3) is hypothesized to act as a ligand for the CLV1 receptor kinase in the regulation of stem cell specification at shoot and flower meristems. CLV3 is a secreted protein, with an amino-terminal signal sequence and a conserved C-terminal domain of 15 amino acids, termed the CLE (CLV3/ESR-related) domain, based on its similarity to a largely unstudied protein family broadly present in land plants. We have tested the function of 13 Arabidopsis CLEs in vivo and found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
186
3
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(199 citation statements)
references
References 24 publications
(23 reference statements)
8
186
3
2
Order By: Relevance
“…b1b2b3c1 plants are phenotypically stronger than clv3 alleles in Col-0, suggesting that multiple CLV3-related ligands might contribute to CLV clade signaling and SAM function in Arabidopsis, as they do in rice (Suzaki et al, 2009). Consistent with this hypothesis, several CLV3-related CLE genes can substitute for loss of CLV3 when expressed from the CLV3 promoter (Ni and Clark, 2006). BAM receptor gene repression represents a specific transcriptional output as a consequence of the CLV1 signaling pathway in RM cells, which is not observed in the homeodomain transcription factor phb phv cna mutants.…”
Section: Discussionsupporting
confidence: 66%
“…b1b2b3c1 plants are phenotypically stronger than clv3 alleles in Col-0, suggesting that multiple CLV3-related ligands might contribute to CLV clade signaling and SAM function in Arabidopsis, as they do in rice (Suzaki et al, 2009). Consistent with this hypothesis, several CLV3-related CLE genes can substitute for loss of CLV3 when expressed from the CLV3 promoter (Ni and Clark, 2006). BAM receptor gene repression represents a specific transcriptional output as a consequence of the CLV1 signaling pathway in RM cells, which is not observed in the homeodomain transcription factor phb phv cna mutants.…”
Section: Discussionsupporting
confidence: 66%
“…CLV1 encodes a receptorlike kinase containing leucine-rich repeat (LRR) motifs, CLV2 a LRR receptor-like protein and CLV3 a small secreted polypeptide (Clark et al, 1997;Fletcher et al, 1999;Jeong et al, 1999;Rojo et al, 2002;Ni and Clark, 2006). Recent findings have shown that transient inactivation of the CLV pathway leads to rapid alterations in the expression of meristem regulators, consistent with earlier studies investigating the effect of clv mutations on WUS expression (Reddy and Meyerowitz, 2005).…”
Section: Introductionsupporting
confidence: 74%
“…Studies on the putative CLE peptides of Arabidopsis (Ito et al, 2006;Ni and Clark, 2006;Strabala et al, 2006;Whitford et al, 2008) have shown a direct relationship between CLE domain sequence and induced phenotypes. MtCLE12 and MtCLE13 are most similar to a group of less characterized Arabidopsis CLE peptides (AtCLE1-AtCLE7) that are broadly produced with higher activity levels in the root (Sharma et al, 2003;Ito et al, 2006).…”
Section: Discussion Cle Family In M Truncatulamentioning
confidence: 99%